PENGARUH MEDIA AUGMENTED REALITY TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV C SDN BARURAMBAT KOTA 1 - Amirotudz Dzofiroh; Kholifatul Hakimah Ameliyanti; Malidina Firah; Rani Nur'aini; Shilfi Rohmatika; Ika Dian Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study has a problem that was found when conducting pre-research, namely regarding the low learning outcomes of students in the Natural and Social Sciences (IPAS) subject in the material of Plant Body Parts and Their Functions in grade IV of elementary school, with a population of 25. This study aims to determine the effect of Augmented Reality (AR) media on student learning outcomes while providing alternative learning media that are innovative and relevant to the development of the times. This study uses a quantitative research type with a one-group design experimental research method. The main data source used in this study is primary data obtained through multiple-choice tests that are separated into a pretest and a posttest. The results of this study indicate that by using Augmented Reality-based media through the Assemblr Edu web, the highest pretest score was 80, and the lowest score was 20, with an average score of 57.6. After the treatment, the highest posttest score was 100, and the lowest score was 60, with an average of 79.6.